Intellectual Education in the Pedagogical System of Andrey Sheptytsky (1899–1914) - Vykhrushch, Anatoliy (Pedagogical Discourse, 2018)
The article describes the most important aspects of intellectual education in the creative heritage of the outstanding thinker Andrey Sheptytsky. Intellectual education is considered as an element of the educational system, which covers all major aspects of life: faith, self-sacrificing work for the benefit of other people, physical health, morality, fighting impurity and drunkenness, diligence, integrity, thrift, avoiding envy and reproach, the right perception of one’s fate and desire to overcome poverty. To understand the essence of intellectual education, Metropolitan Andrey’s appeal to the intelligentsia is important. Attention is focused on boosting listeners’ spirit, prevention of fatigue, appropriate use of humor. Fifteen-minute recollections on the day, as well as the repetition of the main thoughts are important for better memorization. The importance of interest, novelty, significance of moderate passion, simplicity of style, language, imagery, comparison, availability of a conversation, hearing of good sermons of the elders, joint reading, spiritual exercises (recollections) is shown. Specific examples illustrate the importance of uniting nationally minded people, of systemic activities aimed at raising the level of people’s culture, while culture is considered as one of the priorities. The problem of knowing the truth, freedom of choice, the search for causal relationships, mutual complementation the theory and actual facts, the school of prayer, the importance of the national university, the concentration of effort, the problem of rational use of time, the importance of silence in the development of personality are singled out. Within the investigated period, attention is focused on the importance of family education; the role of reading is emphasized. The importance of the common pastoral work and mastering the art of sermon, the need for proper respect for the work of teachers is proved.